Debunking the myths of new product development - Cooper, Robert G.
Robert G. Cooper presents the latest findings from his ongoing research into the factors that separate winning products and timely introductions from losers.
Neither the competitive situation nor being first to market had much impact on the success of these new products. Here are 13 factors that did.
Too many myths prevail about how to manage new product projects. This article probes what truly separates winners from losers in the new product game. It reports the results of a study of 103 new product cases from 21 major firms and divisions in four countries. Key success factors are identified-factors that distinguish the successful projects from the commercial duds. These factors cover a broad spectrum : from elements of competitive advantage to market attractiveness to the way we organize people into project teams. Lessons about how to manage new product projects, and even the types of projects that seem to be most successful, are highlighted. Although the study focuses specifically on the chemical industry, the results appear to have applicability to moderate-to-high tech industries in general.
Keywords: Product development